Attitudes and beliefs about family and domestic violence in faith‐based communities: An exploratory qualitative study. Issue 4 (17th March 2022) - Truong, Mandy; Sharif, Mienah; Olsen, Anna; Pasalich, Dave; Calabria, Bianca; Priest, Naomi
Abstract: Family and domestic violence (FDV) is a major social, economic and health issue that is associated with a range of physical, mental and behavioural health outcomes. Religion and faith are powerful and influential in shaping the lives of many individuals and societies, in addition to the social practices, norms and structures that are significant in understanding and responding to FDV. This study examines the influence of religious beliefs and values on attitudes and beliefs of FDV among culturally diverse faith communities in Australia. Interviews and focus groups were conducted with 64 participants from a range of cultural and religious backgrounds and included faith leaders, community members and FDV sector workers. Overall, findings indicate that tensions exist between expressions of faith and attitudes to women and FDV. Whilst there is general agreement among participants that their faiths did not condone violence, they also identified cultural structures related to their faiths that enabled and ignored abuse against women. Further exploration of these issues within specific faith communities, as well as how to support and engage with these communities in increasing understandings of FDV and developing effective responses, is needed in the Australian context.